Proteomic analyses reveal distinct chromatin‐associated and soluble transcription factor complexes. Issue 1 (21st January 2015) - Li, Xu; Wang, Wenqi; Wang, Jiadong; Malovannaya, Anna; Xi, Yuanxin; Li, Wei; Guerra, Rudy; Hawke, David H; Qin, Jun; Chen, Junjie
Abstract: The current knowledge on how transcription factors (TFs), the ultimate targets and executors of cellular signalling pathways, are regulated by protein–protein interactions remains limited. Here, we performed proteomics analyses of soluble and chromatin‐associated complexes of 56 TFs, including the targets of many signalling pathways involved in development and cancer, and 37 members of the Forkhead box (FOX) TF family. Using tandem affinity purification followed by mass spectrometry (TAP/MS), we performed 214 purifications and identified 2, 156 high‐confident protein–protein interactions. We found that most TFs form very distinct protein complexes on and off chromatin. Using this data set, we categorized the transcription‐related or unrelated regulators for general or specific TFs. Our study offers a valuable resource of protein–protein interaction networks for a large number of TFs and underscores the general principle that TFs form distinct location‐specific protein complexes that are associated with the different regulation and diverse functions of these TFs. Synopsis: Chromatin‐associated and soluble complexes for 56 human transcription factors (TFs), identified by tandem affinity purification followed by mass spectrometry, indicate that distinct binding partners dictate the regulation and functions of TFs. 2, 156 high‐confident interactions are identified by TAP/MS for 56 human TFs, including 37 members of the Forkhead box (FOX) TF family. TFs form distinct complexes on and off chromatin. Different TF‐binding partners dictate the specific regulation and diverse functions of these TFs. Abstract : Chromatin‐associated and soluble complexes for 56 human transcription factors (TFs), identified by tandem affinity purification followed by mass spectrometry, indicate that distinct binding partners dictate the regulation and functions of TFs.